Double pulse laser welding of 6082 aluminium alloys. (January 2015) - von Witzendorff, P.; Hermsdorf, J.; Kaierle, S.; Suttmann, O.; Overmeyer, L.
<x content-type="archive" xml:space="preserve">Abstract</x> Double pulse laser welding is investigated to reduce hot cracking in 6082 aluminium alloy welds. Therefore, Nd:YAG and diode laser pulses are superimposed and synchronised with a specific delay. The diode laser heats the parent metal and weld metal during weld spot solidification to compensate for solidification shrinkage and thermal contraction. The results of conventional pulsed laser welding prove that hot cracking is strongly dependent on the pulse peak power of the Nd:YAG laser, which constrains the crack free penetration depth. Adding the diode laser pulse at a defined time during weld spot solidification eliminated hot cracking. The double pulse welding method allowed the butt welding of 0·5 mm thick 6082 aluminium alloys without the formation of hot cracking.